Efficacy of a novel proprietary dietary supplement (TRI 360TM) on psychological symptoms and stress-related quality of life in adult subjects: A randomized controlled clinical trial - Trivedi, Mahendra Kumar; Branton, Alice; Trivedi, Dahryn; Mondal, Sambhu; Jana, Snehasis (Frontiers in Psychiatry, 2022)
Nowadays, diet plays an increasingly important role in normal physiology and mental health. Recently, many studies have shown that more use of dietary supplements in mental and psychological disorders. Study objective was to investigate safety and efficacy of proprietary nutraceutical combination (TRI 360TM) on psychological symptoms in adult human subjects with one or more psychological symptoms in open-label, single-center, parallel-group, randomized controlled trial. Eighty-four participants aged 20–45 years with psychological symptoms were completed this trial. Participants were randomly assigned to placebo and treatment groups. Treatment group received TRI 360TM capsules twice a day. TRI 360TM was well-tolerated and didn't show treatment-related adverse-events upto 180 days. All assessed perception scorings on psychological symptoms like fatigue, mental stress, sleep disturbance, anxiety, depression, emotional trauma, mood changes, self-confidence, willpower, and motivation were very significantly (p ≤ 0.0001) improved in TRI 360TM participants than placebo control group. Furthermore, significantly (p ≤ 0.001) increased levels of functional biomarkers: vitamin C and D3 metabolites, neurotransmitters, hormones, antiaging protein (klotho) level; and decreased proinflammatory cytokines and oxidative stress marker, malondialdehyde in TRI 360TM group than placebo. According to these findings, the use of TRI 360TM supplementation as a potentially safe therapeutic option for reducing psychological symptoms in healthy adults.